Introducing an adolescent cognitive maturity index - El Damaty, Shady; Darcey, Valerie L.; McQuaid, Goldie A.; Picci, Giorgia; Stoianova, Maria; Mucciarone, Veronica; Chun, Yewon; Laws, Marissa L.; Campano, Victor; Van Hecke, Kinney; Ryan, Mary; Rose, Emma Jane; et al. (Frontiers in Psychology, 2022)
Children show substantial variation in the rate of physical, cognitive, and social maturation as they traverse adolescence and enter adulthood. Differences in developmental paths are thought to underlie individual differences in later life outcomes, however, there remains a lack of consensus on the normative trajectory of cognitive maturation in adolescence. To address this problem, we derive a Cognitive Maturity Index (CMI), to estimate the difference between chronological and cognitive age predicted with latent factor estimates of inhibitory control, risky decision-making and emotional processing measured with standard neuropsychological instruments. One hundred and forty-one children from the Adolescent Development Study (ADS) were followed longitudinally across three time points from ages 11–14, 13–16, and 14–18. Age prediction with latent factor estimates of cognitive skills approximated age within ±10 months (r = 0.71). Males in advanced puberty displayed lower cognitive maturity relative to peers of the same age; manifesting as weaker inhibitory control, greater risk-taking, desensitization to negative affect, and poor recognition of positive affect.